2019
DOI: 10.3390/min9020105
|View full text |Cite
|
Sign up to set email alerts
|

Emerald Deposits: A Review and Enhanced Classification

Abstract: Although emerald deposits are relatively rare, they can be formed in several different, butspecific geologic settings and the classification systems and models currently used to describeemerald precipitation and predict its occurrence are too restrictive, leading to confusion as to theexact mode of formation for some emerald deposits. Generally speaking, emerald is beryl withsufficient concentrations of the chromophores, chromium and vanadium, to result in green andsometimes bluish green or yellowish green cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
87
0
19

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(111 citation statements)
references
References 97 publications
(227 reference statements)
5
87
0
19
Order By: Relevance
“…Re-search by Hewton et al (2013) showed that the elements necessary to form beryl were liberated by inorganic thermochemical sulfate reduction via the circulation of warm basinal brines through siliciclastic, carbonate, and evaporitic rocks (figure 17). The Mountain River green beryl occurrence thus represents a variant of the Type IIB emerald deposit in the classification scheme of Giuliani et al (2019) and suggests the potential for Colombian-type emerald mineralization in northwestern Canada.…”
Section: Country Rockmentioning
confidence: 92%
See 2 more Smart Citations
“…Re-search by Hewton et al (2013) showed that the elements necessary to form beryl were liberated by inorganic thermochemical sulfate reduction via the circulation of warm basinal brines through siliciclastic, carbonate, and evaporitic rocks (figure 17). The Mountain River green beryl occurrence thus represents a variant of the Type IIB emerald deposit in the classification scheme of Giuliani et al (2019) and suggests the potential for Colombian-type emerald mineralization in northwestern Canada.…”
Section: Country Rockmentioning
confidence: 92%
“…Emerald deposits are found on all five continents (figure 10) and range in age from Archean (2.97 Ga for the Gravelotte deposit in South Africa) to Cenozoic (9 Ma for the Khaltaro deposit in Pakistan) (figure 11). Giuliani et al (2019) introduced a new classification scheme in which emerald deposits are divided into two main types depending on the geological environment, and further subdivided on the basis of host rock (table 1) (Behling and Wilson, 2010). The emerald deposits are hosted by Cr-rich (3,000 to 4,000 ppmw) talc-chlorite ± actinolite ± magnetite metabasic rocks of the Muva Supergroup, which have been identified as metamorphosed komatiite (Seifert et al, 2004).…”
Section: Part Ii: Emeraldmentioning
confidence: 99%
See 1 more Smart Citation
“…Ionic substitutions can occur between ions with the same charge or with different charge. For example, the substitution of divalent cations for Al is coupled with the substitution of a monovalent cation for a vacancy at a channel site . In addition, water molecules can accommodate inside the hollow channels within the rings of silica tetrahedral.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the substitution of divalent cations for Al is coupled with the substitution of a monovalent cation for a vacancy at a channel site. [17,18] In addition, water molecules can accommodate inside the hollow channels within the rings of silica tetrahedral. In fact, notwithstanding beryl is nominally anhydrous, it is widely reported that natural and hydrothermal emeralds contain H 2 O or OH groups in the structural channels.…”
Section: Introductionmentioning
confidence: 99%